Best Practices in Local Government - Andrews, Christina [UNESP] (2008)
Best practices seem to be the most long-lived and basic technique of public administration. The decuma, the 10 per cent tax on the production of grain introduced by the kingdom of Syracuse in 241BC, was praised as one of the most advanced techniques of the Hellenistic world and later became a model for Roman provinces (Dudley 1991). Even long before the decuma the idea of best practices was already present. Eridu, in ancient Mesopotamia, is an example of possibly the first best practice; many other human settlements since then followed its basic features (Leick, 2002). Thus, it is impossible to dissociate the idea of best practice from the practices that came to be known as public administration.